An experimental study on precision grinding of silicon using diamond grinding pins - Alao, Abdur-Rasheed; Konneh, Mohamed (Inderscience Enterprises Ltd., 2011)
Silicon substrates are difficult to grind to good surface finishes using conventional machining. Ductile mode machining is often required to have flawless machining but this requires the use of expensive machine tools. However, precision grinding using conventional machine tools could generate large amounts of ductile streaks on ground silicon surfaces under good machining conditions. High wheel rotation, slow feed rate, small indentations and small grain sizes are the practical requirements to realise precision grinding of silicon. Therefore, this study examines the feasibility of quantitative determination of the criteria to realise precision grinding of silicon on an NC milling machine with factorial experimental design. The result shows massive ductile streaks at depth of cut, 20 μm; feed rate, 6.25 mm/min and spindle speed of 70,000 rpm with a 43 nm Ra. Spindle speed affects mostly the surface finish. The combined effects of depth of cut and feed rate on Ra and Rt which add to the complexity in the precision grinding process are investigated.